THE CONTEXTUAL EFFECT OF PLACE OF BIRTH DELIVERY AND BIOPSYCHOSOCIAL DETERMINANTS ON POSTPARTUM DEPRESSION: A MULTILEVEL EVIDENCE FROM YOGYAKARTA - Febrianti, Selvia; Tamtomo, Didik; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2020)
Background: Postpartum depression is a condition that affects 20% women in the first four weeks of the puerperium. Postpartum depression can be affected by biological, psychological, socio-cultural, and economic factors. This study aimed to analyze biopsychosocial factors affecting postpartum depression in Sleman, Yogyakarta.Subjects and Method: This was a cross-sectional study. This study was conducted at 25 delivery places in Sleman, Yogyakarta, in August-September 2019. A sample of 200 postpartum mothers was selected by multistage random sampling. The dependent variable was postpartum depression. The independent variables were traditional treatment, age, education, income, parity, pregnancy status, type of delivery, complication, marital satisfaction, and contextual delivery place. The data were collected by questionnaire and analyzed by a multilevel multiple logistic regression.Results: The risk of postpartum depression increased with delivery with intervention (b= 3.30; 95% CI= 1.57 to 5.02; p<0.001), delivery with complication (b=3.77; 95% CI= 2.25 to 5.28; p<0.001), and age ?35 years (b=0.93; 95% CI=-0.20 to 2.07; p=0.109). The risk of postpartum depression decreased with traditional treatment (b= -1.33; 95% CI= -2.51 to -0.15; p= 0.027), education ?Senior high school (b=-1.98; 95% CI= -3.59 to -0.38; p=0.015), family income ?Rp 1,701,000 (b= -3.55; 95% CI= -5.08 to -2.02; p<0.001), multiparous (b= -1.25; 95% CI= -2.45 to -0.04; p=0.041), intended pregnancy status (b= -3.11; 95% CI= -4.96 to -1.25; p= 0.001), and happy marital satisfaction (b= -1.18; 95% CI= -2.30 to -0.05; p=  0.039). There was strong contextual effect of delivery place on postpartum depression with intra-class correlation (ICC)= 31.6%.Conclusion: The risk of postpartum depression increases with delivery with intervention, delivery with complication, and age ?35 years. The risk of postpartum depression decreases with traditional treatment, education ?Senior high school, family income ?Rp 1,701,000, multiparous, intended pregnancy status, and happy marital satisfaction. There is strong contextual effect of delivery place on postpartum depression.Keywords: Postpartum depression, determinant, delivery placeCorrespondence: Selvia Febrianti. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: selvia.febri11@gmail.com. Mobile: 0811593921Journal of Maternal and Child Health (2020), 5(1): 88-99https://doi.org/10.26911/thejmch.2020.05.01.10